2020
DOI: 10.22227/1997-0935.2020.9.1285-1296
|View full text |Cite
|
Sign up to set email alerts
|

To the question of concrete creep in the soil environment

Abstract: Introduction. Concrete creep coupled with specific soil properties represent a problem for the analysis of reinforced concrete structures in geotechnical engineering. The mission of this research is to make a problem statement and to outline its potential solutions. Materials and methods. In the course of the research, the finite element method was applied and the review of works, covering various problem aspects, was performed. Results. Concrete creep in respect of a diaphragm wall is most vividly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…For the cost-effective design of pit enclosure structures and assessing the impact of construction on the surrounding buildings in the corner zones, it is necessary to perform calculations in a three-dimensional formulation of the problem. It is also advisable to take into account the nonlinear work of concrete, since it was found that the creep of concrete affects the distribution of forces in depth and leads to a decrease in the flexural stiffness of reinforced concrete structures [8].…”
Section: Resultsmentioning
confidence: 99%
“…For the cost-effective design of pit enclosure structures and assessing the impact of construction on the surrounding buildings in the corner zones, it is necessary to perform calculations in a three-dimensional formulation of the problem. It is also advisable to take into account the nonlinear work of concrete, since it was found that the creep of concrete affects the distribution of forces in depth and leads to a decrease in the flexural stiffness of reinforced concrete structures [8].…”
Section: Resultsmentioning
confidence: 99%
“…To determine the values of the actual bending moments that occur in the diaphragm wall in the ground, it is also necessary to correctly determine the stiffness of the structure (Sapin and Diakonov 2019). At the same time, it is necessary to take into account the non-linear nature of the work of reinforced concrete, since when the moment of cracking is exceeded, the rigidity of the structure drops significantly [12,13]. In accordance with this, it is necessary to plot the relationship between the bending moment acting on the wall and its stiffness (EI).…”
Section: Methodsmentioning
confidence: 99%
“…The boundary conditions for the model of moisture transport in saturated concrete according to Darcy's law will be water pressure at the contact with structure, and environmental relative humidity for unsaturated concrete under to the Bažant-Najjar model. Since soil is the environment for such structures as piles or diaphragm walls, it is necessary to take into account the relative humidity of soil environment [17]. Then the boundary conditions at soil contact with the geotechnical structures can be characterized by such parameters as temperature, the pore pressure and the relative humidity of the environment.…”
Section: Introductionmentioning
confidence: 99%